THE ROLE OF ACCRUAL ACCOUNTING AND TRANSPARENCY IN ECONOMIC SUSTAINABILITY - Shafira, Andi Nur Ram; Furqan, Andi Chairil; Paranoan, Selmita (Universitas Riau, 2025)
This study examines the effect of accrual-based accounting and fiscal transparency, measured through the Corruption Perceptions Index (CPI), on economic sustainability. The analysis uses panel data from 156 countries over the period 2022–2024, resulting in 438 observations. Employing a random-effects regression model, the findings demonstrate that accrual accounting significantly strengthens economic sustainability by improving the quality of financial reporting and enhancing fiscal accountability. Similarly, fiscal transparency, proxied by higher CPI scores, exerts a positive and significant influence by fostering public trust and institutional stability. Conversely, GDP per capita, included as a control variable, does not show a significant effect, indicating that economic capacity alone cannot guarantee sustainability without effective governance. The study contributes theoretically by integrating Sustainable Development Theory and Stakeholder Theory into fiscal governance and provides empirical novelty by simultaneously testing accrual accounting and transparency across countries. Practically, the results underscore the strategic role of governments, auditors, and international institutions in advancing accrual adoption and transparency reforms to sustain long-term economic development.